Langerhans Hucreli Histiyositoz Tanili Hastada Soliter Kemik Lezyonunun Takibinde Kemik Sintigrafi ve SPECT/BT'nin Rolu - TUROĞLU, HALİL TURGUT; İNANIR, SABAHAT; ÖZGÜVEN, SALİH; KESİM, SELİN; ERDİL, TANJU YUSUF (GALENOS YAYINCILIK, 2021)
Langerhans' cell histiocytosis (LCH) is a rare disease observed in childhood characterized by the proliferation of Langerhans' cells resulting in focal or systemic manifestations (including the bones). Here, we present a pediatric case with a localized biopsy-proven LCH, who underwent progression from solitary to multifocal form detected on bone scintigraphy and single photon emission computerized tomography/computed tomography (SPECT/CT) performed within four months. Emphasizing on localized bone pain (predictive of osseous LCH) and local tenderness and swelling usually guides the nuclear physician to perform additional SPECT/CT with presumably an improvement of the diagnostic accuracy as demonstrated in our case.
Keywords: Langerhans' cell histiocytosis; technetium-99m-methylene diphosphonate bone scintigraphy; bone SPECT/CT; EMISSION TOMOGRAPHY/COMPUTED TOMOGRAPHY; CELL HISTIOCYTOSIS; BONE-SCINTIGRAPHY; LESIONS